Kurikulum Kerjasama sebagai Upaya Penguatan Kompetensi SMK Pusat Keunggulan - Lucky Rafli Abdillah; Fantika Febry Puspitasari (Ideguru: Jurnal Karya Ilmiah Guru, 2025)
Professional and quality human resources (HR) services are highly dependent on the existence of a reputable organization. The only way to fulfill these requirements is through a reputable educational institution. It is hoped that competitive Human Resources (HR) will be created at national, regional and international levels through quality education. A good sign of a quality Islamic educational institution is its track record in both academic and extracurricular fields, as well as national and international accreditation status. In an effort to improve the level of Islamic education in Indonesia, this research examines the quality management system used by educational institutions. The principal, deputy principal, head of department, and resource persons were additional research informants at SMK Muhammadiyah 7 Gondanglegi. This research combines a descriptive approach with qualitative methods to describe field research findings. The use of qualitative descriptive methods makes it easier for researchers to explain research results by describing the steps taken by SMK Mutu in determining curriculum and strategies to improve student skills, especially in the Automotive Light Vehicle Engineering (TKRO) department as a Center of Excellence. Research findings show that improving the quality of student competency at Muhammadiyah 7 Gondanglegi Vocational School is by implementing a collaborative curriculum with industry, namely by aligning the curriculum, project-based learning, bringing in teachers from industry and carrying out TEFA activities. In addition, educational institutions plan well and implement their plans as intended, which directly affects the quality and progress of these institutions.